R. A. M. STERN, J. STAMP (eds.) - Pedagogy and Place: 100 years of architecture education at Yale - Sentieri Omarrementería, Carla (ZARCH, 2019)
Robert A. M. Stern y Jimmy Stamp (eds.)Pedagogy and Place: 100 years of architecture education at YaleYale: Yale University Press, 2016, 654 páginas. Tapa dura. Idioma: inglés. $65.00.ISBN-13: 978-0300211924; ISBN-10: 9780300211924